Admission via the emergency department in relation to mortality of adults hospitalised with community-acquired pneumonia: an analysis of the British Thoracic Society national community-acquired pneumonia audit. Issue 1 (30th July 2014) - Rodrigo, Chamira; Mckeever, Tricia M; Woodhead, Mark; Welham, Sally; Lim, Wei Shen
Abstract : Objective: To determine the association between 30-day inpatient mortality and route of admission to hospital, for adults with community acquired pneumonia (CAP). Methods: We studied 16 313 adults included in the British Thoracic Society (BTS) national CAP audit dataset. Comparisons were made between adults admitted via emergency departments (ED) with non-ED routes of admission, with regard to 30-day inpatient mortality. Secondary outcome measures were adherence to national CAP guidelines (time to first chest X-ray ≤4 h from admission; time to first antibiotic dose ≤4 h from admission; antibiotic choice; and antibiotic route of administration) by route of admission. Results: Of adults hospitalised with CAP, 75.6% were admitted via ED; these adults had a greater prevalence of comorbid illness and higher disease severity in comparison with non-ED admissions. Adjusted 30-day inpatient mortality was similar for ED versus non-ED route of admission (OR 1.10, 95% CI 0.96 to 1.25). Admissions via ED were associated with faster processes of care (time to chest X-ray ≤4 h, adjusted OR 3.39, 95% CI 2.79 to 4.12; time to first antibiotic ≤4 h, adjusted OR 1.62, 95% CI 1.42 to 1.84) and greater use of intravenous antibiotics regardless of disease severity (adjusted OR 1.58, 95% CI 1.43 to 1.74). Conclusions: Adults with CAP admitted via EDs have more comorbid illness and greater disease severity compared to those admitted via non-ED routes. Following adjustment for these differences, 30-day inpatient mortality was not associated with route of admission.